2011
DOI: 10.3758/s13414-011-0131-9
|View full text |Cite
|
Sign up to set email alerts
|

Halt and recovery of illusory motion perception from peripherally viewed static images

Abstract: We quantitatively investigated the halt and recovery of illusory motion perception in static images. With steady fixation, participants viewed images causing four different motion illusions. The results showed that the time courses of the Fraser-Wilcox illusion and the modified Fraser-Wilcox illusion (i.e., "Rotating Snakes") were very similar, while the Ouchi and Enigma illusions showed quite a different trend. When participants viewed images causing the Fraser-Wilcox illusion and the modified Fraser-Wilcox i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…They claimed that the illusion is caused directly by adaptation over time, rather than being driven by eye movements, suggesting that changes over time in the adapted states of visual neurons are sufficient to evoke a strong percept of motion (Petrov and Popple 2002). Tomimatsu et al (2011) also confirmed the crucial role of adaptation in the Fraser-Wilcox Illusion. Other authors stressed the crucial role of the fixational eye movements in eliciting the illusory motion.…”
Section: Introductionsupporting
confidence: 62%
“…They claimed that the illusion is caused directly by adaptation over time, rather than being driven by eye movements, suggesting that changes over time in the adapted states of visual neurons are sufficient to evoke a strong percept of motion (Petrov and Popple 2002). Tomimatsu et al (2011) also confirmed the crucial role of adaptation in the Fraser-Wilcox Illusion. Other authors stressed the crucial role of the fixational eye movements in eliciting the illusory motion.…”
Section: Introductionsupporting
confidence: 62%
“…Thus, the afterimages and focus rotation should contribute not only to the afterimage stage but also to the other stages that lead to the peripheral drift illusion, including the eye-opening and gaze stages. Indeed, the illusory rotation by the second FW stimulus is interfered if the first and second FW stimuli are repetitively presented at a short inter-stimulus interval [27] , implying the contribution of afterimages to this illusion. This discussion suggests that our retinal ON/OFF model may provide a systematic framework to understand the mechanisms underlying the peripheral drift illusion at all of its stages.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported that infants [20], fish [21], and cats [22] also perceive the RSI, and the intensity of the illusion decreases by age [23]. The effects of contrast [15], color [24], and afterimages [25] have also investigated in previous studies. In addition, a video prediction machine using deep neural networks has been found to perceive the RSI [26].…”
Section: Related Workmentioning
confidence: 98%